PENGEMBANGAN E-MODUL BERBASIS ANDROID PADA MATA PELAJARAN KOMPUTER DAN JARINGAN DASAR UNTUK KELAS X TKJ DI SMK N 2 PEKANBARU - Cicillya Selly Maivi; Ganefri Ganefri; Sukardi Sukardi (Jurnal Informatika, 2021)
Based on the observations at Computer and Network Engineering program in Vocational High School 2 Pekanbaru, modules utilized in Computer and Network Basic subjects are not optimal. It very well may be seen from the absence of student motivation when reading the modules, because the modules is not interesting and still in form of paper sheets that must be photocopied first. Students still rely on teacher for getting information during learning. Based on it, this research aims to develop an Android based e-module on Computer and Network Basic subjects that are valid, practical and effective as an independent learning alternative that can be utilized independently by students. This research uses Research and Development (R & D) and Instructional Development Institute (IDI). And the advancement model comprising of three phases : define, develop and evaluate. The instrument utilized in this research is a questionnaire, that utilized to measure the validity and the practicality of Android-based e-module. Meanwhile, to measure the effectiveness uses multiple choice questions as instrument. The outcomes showed that the Android-based e-module are valid based on the validation on each aspect by the validator. Android-based e-modules are practical based on teacher / practitioner and student response. By comparing the learning outcomes of students before and after utilizing e-module, the learning result raise by 14% after learning used e-module. It means that Android-based e-module is effectively utilized as an alternative learning media that can be studied independently by students in improving learning outcomes.